Inhibitory, biocompatible, and pharmacological potentiality of dammarenolic‐acid derivatives towards α‐glucosidase (3W37) and tyrosine phosphatase 1B (PTP1B). Issue 2 (17th April 2022) - Quy, Phan Tu; Van Hue, Nguyen; Bui, Thanh Q.; Triet, Nguyen Thanh; Van Chen, Tran; Van Long, Nguyen; Smirnova, Irina; Petrova, Anatasia; Thao, Tran Thi Phuong; Ninh, Pham Thi; Ha, Nguyen Thi Thu; Nhung, Nguyen Thi Ai
Abstract: Dammarenolic‐acid derivatives experimentally demonstrated possessing inhibition activity towards α ‐glucosidase might be used as the evidence to retrieve an inhibitory mechanism and subjected for computational screening on other diabetes‐related proteins, e.g. tyrosine phosphatase 1B. Seven structures reported in our preceding work (denoted as 1‐7) were subjected for an in silico investigation in this study on inhibitability towards protein structure PDB‐3W37 by molecular docking simulation. The computer‐based results see a good agreement with those from laboratory‐based reports, with the order of static stability: 3‐3W37 > 1‐3W37 > 7‐3W37 > 2‐3W37 > 6‐3W37 5‐3W37 4‐3W37 (negligible activity). Together, experiment‐theory reveals the most promising candidates are 1‐3 and 7 . The in‐theory order for most promising inhibitors regarding protein structure UniProt‐PTP1B is: 1‐PTP1B > 6‐PTP1B > 4‐PTP1B . Quantity‐structure relationship analyses (i.e. QSARIS and ADMET) expect 1‐3 as compounds with sufficient bio‐ and pharma‐compatibility. Altogether, the results specify 1 as the most promising candidate for multi‐purpose inhibition towards diabetes‐based proteins, thus encouraging elevated efforts for validation and further development for application.